2018
DOI: 10.1016/j.archoralbio.2017.12.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical stiffness of TMJ condylar cartilage increases after artificial aging by ribose

Abstract: The present model, in which ribose was used to mimic certain aspects of age-related changes, can be employed as an in vitro model to study age-related mechanical changes in the TMJ condyle.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 50 publications
(71 reference statements)
1
10
0
Order By: Relevance
“…3). We previously showed that incubation of porcine TMJ condyles with ribose as an aging-effect simulation increased Pen level and consequently the stiffness of the cartilage 28 . Positive correlations between Pen increase on stiffening of cartilage has been also shown in natural aging both in hyaline cartilage and in fibrocartilage of TMJ disc form different species 6,14,29 .…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…3). We previously showed that incubation of porcine TMJ condyles with ribose as an aging-effect simulation increased Pen level and consequently the stiffness of the cartilage 28 . Positive correlations between Pen increase on stiffening of cartilage has been also shown in natural aging both in hyaline cartilage and in fibrocartilage of TMJ disc form different species 6,14,29 .…”
Section: Discussionmentioning
confidence: 98%
“…The origin of the seemingly contradictory findings could be related to several parameters that have changed with aging, e.g., Pen level, GAG, and the region of the cartilage. Firstly, in a previous study, we measured a 50 fold increase in Pen levels leading to a 1.5 fold increase in stiffness 28 . The crosslink level of naturally aged samples in this study was only 15-fold higher than the young samples.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations